Rapid evolution of an RNA virus to escape recognition by a rice nucleotide‐binding and leucine‐rich repeat domain immune receptor. Issue 3 (7th December 2022) - Bonnamy, Mélia; Pinel‐Galzi, Agnès; Gorgues, Lucille; Chalvon, Véronique; Hébrard, Eugénie; Chéron, Sophie; Nguyen, Tràng Hiếu; Poulicard, Nils; Sabot, François; Pidon, Hélène; Champion, Antony; Césari, Stella; et al.
Summary: Viral diseases are a major limitation for crop production, and their control is crucial for sustainable food supply. We investigated by a combination of functional genetics and experimental evolution the resistance of rice to the rice yellow mottle virus (RYMV), which is among the most devastating rice pathogens in Africa, and the mechanisms underlying the extremely fast adaptation of the virus to its host. We found that the RYMV3 gene that protects rice against the virus codes for a nucleotide‐binding and leucine‐rich repeat domain immune receptor (NLRs) from the Mla‐like clade of NLRs. RYMV3 detects the virus by forming a recognition complex with the viral coat protein (CP). The virus escapes efficiently from detection by mutations in its CP, some of which interfere with the formation of the recognition complex. This study establishes that NLRs also confer in monocotyledonous plants immunity to viruses, and reveals an unexpected functional diversity for NLRs of the Mla clade that were previously only known as fungal disease resistance proteins. In addition, it provides precise insight into the mechanisms by which viruses adapt to plant immunity and gives important knowledge for the development of sustainable resistance against viral diseases of cereals.